Early childhood screen time and psychopathology in a Portuguese Sample - Sofia Pires; Mariana Pessoa; Ana Vera Costa; Susana Santos; Vânia Martins; Joana Calejo Jorge (Universidade de Fortaleza, 2022)
Objective: To characterize the habits of screen exposure time in a sample of infants and preschoolers and to assess if there is a relationship between the proportion of early childhood excessive screen exposure time and the presence of psychopathology and parental concerns. Methods: A cross-sectional cohort study was conducted with 38 infants and preschoolers in a Child and Adolescent Psychiatric outpatient unit and children followed exclusively in Primary Health Care in the same geographic area (Vila Nova de Gaia/ Espinho Hospital Center). Information was collected from a self-report questionnaire filled by the caregiver between October 1st, 2018, and June 30th, 2019. Results: Screen time was analyzed and organized in two groups: the H group (screen time higher than recommended) and R group (within the recommended), according to the American Academy of Pediatrics. The need for referral to a Child and Adolescent Psychiatry appointment and the presence of parental behavior concerns related to behavior changes during early childhood are significantly associated with screen time, with a greater proportion within the H group (71.8% (n=15) vs. 31.3% (n=6), p=0.006 for the appointment and 61.1% (n=13) vs. 25% (n=4), p=0.032 for behavior concerns). There is also a tendency towards a higher percentage of overweight/obesity, sleep and food-related concerns in the H group. Only 45% of the total sample fulfilled the recommendations regarding screen exposure (p value ≤0.05). Conclusion: The study found an association between screen exposure time above the recommended and presence of psychopathology and parental concern for behavioral changes. These findings were statistically significant.